WORKPLACE SMOKING POLICIES - RANSOME, SHARON (Tufts Archival Research Center, 2007)
Handwritten; Memorandum from Sharon Ransome to Bob Moore regarding workplace smoking policies. Mentions appendix of the Bureau of National Affairs (BNA) report listing various levels of smoking restrictions. Discusses the difficulty in estimating how many corporate businesses that have adopted smoking policies.